Exploring simple linear regression model through fuzzy regression approach - Dulla, Lavina B.
Abstract (The exploration of simple linear regression model through fuzzy regression approach attempts to present that fuzzy regression can be used as possible alternative to classical regression. It likewise seeks to assess the parameter estimates between linear regression and fuzzy regression and to evaluate the differences and characteristics of linear regression and fuzzy regression using the width of prediction interval, mean absolute deviation and variance of residuals. Based on the simple linear regression model, the fuzzy regression approach is worth considering as an alternative to simple linear regression when the sample size is between 10 and 20. As the simple size increases, fuzzy regression approach is not appropriate to use since the assumption regarding large sample size is already operating within the framework of simple linear regression. Nevertheless, it can be recommended for practical alternative when decisions often have to be made on the basis of small data).
July 2017.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Linear Regression; Regression Approach